Analysis of suboptimal stent deployment using intravascular ultrasound and coronary pressure pullback measurement. Issue 4 (April 2017) - Tanaka, Nobuhiro; Pijls, Nico H.J.; Yamashita, Jun; Kimura, Yo; Ogawa, Masashi; Murata, Naotaka; Sakoda, Kunihiro; Hoshino, Kou; Hokama, Youhei; Yamashina, Akira
Abstract: Background: There are some cases in whom a sufficient improvement in fractional flow reserve (FFR) could not be achieved even if anatomical results indicated satisfactory stent deployment. We investigated the relation of abnormal findings between intravascular ultrasound (IVUS) and coronary pressure pullback measurement (CP-PB). Methods: IVUS and CP-PB were investigated after stent deployment in 60 vessels in 53 patients. CP-PB criterion for adequate stent deployment was defined as a ratio of coronary pressure at the stent distal edge to the proximal edge (Psd/Psp) that is greater than 0.95. Results: Residual pressure gradient across the stent which was indicated by Psd/Psp ≤ 0.95 was present in 11 (18%), and four of them were caused by insufficient stent expansion (incomplete apposition and asymmetric dilation), and five of them were caused by issues with stent edge (edge dissection and incomplete coverage of the plaques). Insufficient FFR recovery which was recorded at distal part of target vessel was present in 10 (17%), and the main causes corresponded to inadequate stent deployment in half of the lesions, and presence of residual lesion at a non-stent segment in the other half. There were six lesions in whom Psd/Psp was ≤0.95 but FFR was ≥0.80. Disagreement between IVUS and CP-PB findings was seen in 12 (20%). Conclusions: Residual pressure gradient across the stent can reflect not only an insufficient stent expansion but also issues with stent edges. The decision of optimum stent deployment as assessed by IVUS and CP-PB was mismatched in 20% of cases, therefore careful attention should be paid to decoding the CP-PB findings.